Kenabian dan Nabi Palsu Modern - Mateus Mali (Jurnal Orientasi Baru, 2013)
A prophet and his or her prophecy are theologically inseparable as well as in view of Gods plan of salvation revealed through the life of prophets in history. Without the prophets and their prophecy, human history will remain as nomenclature of events rather than a history of salvation. It will remain merely chronos rather than kairos. How do we figure out a true prophet of God than a false one? How do we find a prophet in our world today, a truly servant of God who spoke Gods justice and righteousness, even in front of a threatening forces that prefer injustice and unrighteousness?